(3GdHYO GdESJQGJjLj dJbjje GdCOGA GdeJhGRfs - (3eMeO eMehO(B, (3jhSas ((3GdbGgQI(B:s (3efThQGJ GdefXeI GdYQHjI ddJfejI GdEOGQjI(B,s, 2005)
(3jVe GdJMdjd GdeGdj hJbjje GdCOGA, GdEWGQ GdYGe ddJMdjd GdeGdj, WQb hCSGdjH GdJMdjd GdeGdj, JWHjbGJ heMOOGJ GSJNOGe GdJMdjd GdeGdj, GdfeGPL GdeYGUQI ddJbjje eDSSj GdGOGA, GdCOGA GdeDSSj hGJLGgGJg GdeYGUQI, GdJMdjd GdeGdj hGdHYO GdESJQGJjLj ddJbjje GdeJhGRf dCOGA GdeDSSI, GdeMGhQ GdCSGSjI ddJbjje GdeJhGRf ddCOGA, ebGjjS GdCOGA GdeJhGRf hGSJQGJjLjI GdeDSSI, HQfGeL EOGQI GdeDSSI dJWHjb fXGe GdJbjje GdeJhGRf ddCOGA, eQGMd JWHjb GdJbjje GdeJhGRf, HWGbI GdJbjje GdeJhGRf ddCOGAs
(3HHdjhZQGajG(B: (3U(B.237s
Keywords: (3GdEbJUGO GdJMdjdjs; (3Jbjje GdCOGAs